Comparison of cefazolin, cefamandole, vancomycin, and LY146032 for prophylaxis of experimental Staphylococcus epidermidis endocarditis. - Wheat, L J (1988)
We evaluated antibiotic prophylaxis in the rabbit model of experimental endocarditis with three strains of Staphylococcus epidermidis of differing susceptibility patterns. For the first strain, which was highly susceptible to methicillin and cephalosporins, vegetations grew S. epidermidis for all 15 untreated rabbits compared with 1 of 20 rabbits receiving cefazolin, 3 of 20 receiving cefamandole, none of 20 receiving vancomycin, and none of 20 receiving LY146032. For the second strain, which was methicillin resistant but cephalosporin susceptible, vegetations were positive for 14 of 15 untreated controls, 4 of 20 receiving cefazolin, 5 of 22 receiving cefamandole, none of 20 receiving vancomycin, and none of 20 receiving LY146032. For the third strain, which was methicillin resistant and only intermediately susceptible to cephalosporin antibiotics, vegetation cultures were positive for 15 of 17 untreated controls, 14 of 21 receiving cefazolin, 11 of 20 receiving cefamandole, 5 of 20 receiving vancomycin, and 0 of 22 receiving LY146032. In conclusion, these studies in the endocarditis model indicate that cefazolin and cefamandole have some protective value against certain strains of S. epidermidis. Vancomycin and LY146032, however, were more active than cephalosporins for all three strains included in this analysis. These findings support the need for trials of vancomycin and LY146032 prophylaxis in patients undergoing placement of prosthetic heart valves.